2010
DOI: 10.1136/oem.2009.051466
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of extrapleural malignant mesothelioma and asbestos exposure, from the Italian national register

Abstract: The rarity of the disease, the low specificity of diagnosis and difficulties in identifying the modalities of asbestos exposure call for caution in discussing aetiological factors other than asbestos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 26 publications
4
38
0
Order By: Relevance
“…The severity of asbestos exposure in the shipbuilding and maintenance industry as well as the high incidence of pleural mesotheliomas in the shipyard areas has been well documented [9]. The prolonged latency period (59 years) found in the current study is consistent with other studies [16,27]. Marinaccio et al [16] reported the mean latency of 48 years among household exposed mesothelioma cases which was significantly longer than that of 43 years observed among the occupationally exposed ones.…”
Section: Ijomeh 2017;30(3)supporting
confidence: 90%
See 4 more Smart Citations
“…The severity of asbestos exposure in the shipbuilding and maintenance industry as well as the high incidence of pleural mesotheliomas in the shipyard areas has been well documented [9]. The prolonged latency period (59 years) found in the current study is consistent with other studies [16,27]. Marinaccio et al [16] reported the mean latency of 48 years among household exposed mesothelioma cases which was significantly longer than that of 43 years observed among the occupationally exposed ones.…”
Section: Ijomeh 2017;30(3)supporting
confidence: 90%
“…Their exposure was only through residential inhalation of asbestos from husband's or father's contaminated work clothes that were not removed in the workplace for cleaning but or unknown (e.g., questionnaires reported an incomplete job and/or residential and familial history) following the National Guidelines [15,16]. Certain occupational exposure is attributed to the subjects whose work has involved the use of asbestos or materials containing asbestos; probable occupational exposure to the subjects who have worked in a firm where asbestos has been certainly used but whose exposure cannot be documented; possible occupational exposure to the subjects who have worked in a firm referring to an economic sector where asbestos has been used [15,16]. Exposure information and medical data were reviewed (by occupational physicians) in all cases included for the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations